Evaluation of Contemporary ELTTextbooks in Light of the Recent Developments in Language Pedagogy - Jafari, Kian (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Materials play an indispensable role in the teaching and learning of languages. However, the research to date has noted that recently materials have not received sufficient attention in applied linguistics. Moreover, very few related studies have explored contemporary ELT materials in light of the recent developments in language pedagogy.Thisstudy therefore, surveyed 10 contemporary ELT textbooks for the primary level, published by Oxford, Pearson and Cambridge, respectively. The ELT textbooks were reviewed in terms of the representation of the English language use and users as well as the 21st century skills and cross-curricular learning. Evaluation of the contemporary English instructional materials revealed that the mostly feature the fictional young language learner, of the Caucasian origin, in the familiar contexts of English use. This representation does not reflect the current socio-linguistic status of the language. Further, the textbooks under review appear, although to a different extent, to develop and promote a range of the 21st century skills as well as contribute to young English language learners’ cross-curricular learning. In this regard, the study offers some implications and makes suggestions for future research. Keywords: contemporary ELT textbooks, English language use, users of English, the 21st century skills, cross-curricular learning

ÖZ : Ders materyalleri dil öğrenimi ve öğretiminde çok önemli bir rol oynar. Ancak bugüne kadar yapılan araştırmalar ders materyallerine Uygulamalı Dilbiliminde son zamanlarda yeterli önemin verilmediğini göstermektedir. Ayrıca, çağdaş materyaller üzerinde, dil öğretimindeki son gelişmeler ışığında çok az sayıda araştırma yapılmıştır. Bu nedenden dolayı bu araştırma ilkokul düzeyinde Oxford, Pearson ve Cambridge yayınevleri tarafından basılan 10 güncel ders kitabını incelemiştir. Ders kitapları, İngiliz dili kullanımı ve dil kullanıcılarının temsiliyetiyanısıra 21. Yüzyıl yetileri ve müfredatlar arası öğrenim açısından incelenmiştir. Güncel İngilizce öğretim materyallerinin değerlendirilmesi göstermiştir ki İngilizce kullanılan doğal ortamlarda temsili genç dil öğrencisinin en belirgin özelliği Kafkas kökenli olmasıdır. Bu temsiliyet İngilizce dilinin güncel sosyal ve dilbilimsel statüsünü yansıtmamaktadır. Buna ek olarak, incelenen ders kitaplarının farklı derecelerde birtakım 21. Yüzyıl yetilerinin gelişmesinde etken olduğunu ve öğrencilerin interdisipliner öğrenimlerine katkıda bulunduğunu göstermiştir. Bu araştırma, konuyla ilgili bazı ipuçları vermekte ve gelecekteki araştırmalara ışık tutmaktadır. Anahtar kelimeler: çağdaş İngilizce dil öğretimi materyalleri, İngiliz dili kullanımı, İngiliz dili kullanıcıları, 21. Yüzyıl yetileri, müfredatlar arası öğrenim
Master of Arts in English Language Teaching (ELT). Thesis (M.A.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2016. Supervisor: Prof. Dr. Gülşen Musayeva Vefalı.
Keywords: English Language Teaching (ELT); English Language - Study and Teaching - Textbooks - Evaluation; Contemporary ELT textbooks; English language use; users of English; the 21st century skills; cross-curricular learning